(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
The research aims to know the nature of the relationship between the ethical behavior of senior management and guest satisfaction in first-class hotels in the holy city of Karbala, represented by the hotels (Baron, Hoda Al-Wali, Rotana Rayhaan Karbala and Damas), and based on the importance of the research topic in hotel organizations and the influence that these organizations have in society. The research problem was embodied in a central question: What is the effect of the ethical behavior of senior management in enhancing guest satisfaction in the hotels studied? The research adopted the descriptive analytical method in completing the research by collecting data. A questionnaire form was used to collect data that was distributed to a purposive sample of (80) Respondents were represented by (hotel managers and their assistants, department managers and their assistants, and front-line activity officials who have direct contact with the guests), and the research included two main hypotheses, which were subjected to appropriate statistical analysis. It was used in the (SPSS v23) statistical program for frequency distribution, graphical shapes, and percentages. Weighted arithmetic mean, standard deviation, relative importance (severity of answer), Spearman’s rank correlation coefficient, simple Pearson correlation coefficient, simple linear regression coefficient, multiple regression coefficients, coefficient of determination R2, F test (F-test), sequential regression test, Which gave numerical results, a set of recommendations were arranged, the most important of which was to enhance the ethical behaviors of the senior administrative leadership in hotel organizations by activating the activities and capabilities available to hold training courses, seminars, and workshops to instill moral values and effective behavior in them to enhance guest satisfaction